Nutritional Composition and Sensory Evaluation of Cakes Fortified With Plantain, Soybeans and Sesame Seed for Sustainable Economic Development - Omolara Bosede Ogbonyomi; Diana, O. Arubayi; Juliana Ego Azonuche (Budapest International Research and Critics University, 2023)
Cakes represent a convenient and readily consumable baked product, playing a vital role as a significant food item. They contribute to sustainable economic development, employment opportunities, and poverty alleviation, particularly within the baking sector. In Nigeria, fostering the production of cakes that are both nutrient-dense and affordable involves fortifying them with locally available food materials. This study investigates the nutritional composition and sensory attributes of cakes fortified with plantain, soybeans, and sesame seeds, aiming to contribute to sustainable economic development. To achieve this, six distinct blends of composite flours were developed, combining plantain, soybeans, sesame seeds, and wheat flour at varying ratios: 85:5:5:5, 80:10:5:5, 75:10:10:5, 70:15:5:10, 60:10:15:15, and 55:15:15:15. Cake samples were prepared from these blends, with the control being cakes made solely from 100% wheat flour. The samples were coded as follows: WPSS1 to WPSS7. Nutritional and sensory evaluations were conducted on these samples. The nutritional analysis revealed a statistically significant increase (p>0.05) in the nutritional content of cakes fortified with plantain, soybeans, and sesame seed flour across all composite blends. Interestingly, there was no significant difference (p<0.05) in panelist ratings for texture, flavor, taste, mouthfeel, and overall acceptability between the composite cake samples and the control (100% wheat flour cake). The respondents unanimously agreed that composite flours can serve as a means for sustainable economic development. A composite cake consisting of 15% of each fortificant (plantain, soybean, and sesame seed flour) with 55% wheat flour substitution demonstrated the highest nutritional value. Meanwhile, a cake made with 10% plantain, 5% soybean, 5% sesame seed, and 80% wheat flour received the best mean ratings in sensory evaluation among the samples. These results suggest that incorporating plantain, soybean, and sesame seed in the bakery industry can enhance the nutritional profile of cakes, diversify the use of these crops, reduce post-harvest losses, and mitigate the need for foreign exchange spent on wheat importation in regions where wheat cultivation is not viable due to climatic reasons.